Principles of the teaching of nation and state life in the Constitution of Medina - Wildan, T. (IBDA` : Jurnal Kajian Islam dan Budaya, 2023)
Many lessons can be drawn and learned for the lives of Muslims from the guidance in the hadiths of the Prophet. Through the Medina Charter itself, the Prophet Muhammad also taught Muslims social attitudes. During the Prophet Muhammad’s life in Medina there was a multicultural society which included ethnic and cultural pluralism, with differences in culture, religion and ethnicity/race. Articles in the Constitution of Medina show the order and guidelines for the way of life of the state, and can be used for teaching people about the life of the nation and state. This study aims to establish how the ideal principles in such teachings are contained in the Constitution of Medina so that they can be implemented in the life of the nation in Indonesia today. The research methodology was based on a literature study approach, with the content analysis method used in relation to the Constitution of Medina. As for the results and research findings, the pillars of the teachings on state life in the Constitution of Medina are trust, obedience, justice, deliberation, equality, unity, freedom, recognition and protection of human rights, free trials, peace and prosperity.